Agile Leadership in Practice Applying Management 3.0 - Maximini, Dominik (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book illustrates the agile transformation journey of a consulting organization. It consists of nine main chapters, each focusing on specific aspects of transformation. These include establishing value in business, holistic recruitment and retention, innovating performance appraisals, rethinking organizational structure, redesigning leadership roles, streamlining measurement and reward systems, and improving career paths. Some specific processes, such as corporate decision making, SMILE (budget for business improvement at employee discretion), project selection, holiday leave, and career coaching are also described. All of the transformations described build up on Management 3.0, a collection of management principles and practices that fit perfectly in an agile world. The book is of practical relevance for managers and agile coaches who want to learn how to approach agile transformation.
Keywords: Industrial organization; Personnel management; Strategic planning; Leadership; Project management; Organization; Human Resource Management; Business Strategy and Leadership; Project Management